Fast architecture, slow architecture: learning through cross-curricular workshops - Cabrero-Olmos, Raquel (Cuadernos de Proyectos Arquitectónicos, 2019)
Abstract The generational change observed in students in today’s classrooms calls for a revision of traditional ways of teaching and learning architecture. The purpose of this paper is to share an experience teaching the subject Proyectos ( from here onwards to be referred to as Projects), based on an innovative proposal that involved combining different paces of work and design thinking in order to learn design methodology. On the one hand, the subject unfolds in the course of the whole semester; this we call ‘slow architecture’. In between, we insert several sporadic transversal workshops using a dynamic methodology; this we call ‘fast architecture’. A more agile pace of learning is incorporated to adapt to the needs of a new generation of students. It allows a global vision of the project cycle, with more immediate feedback on the proposals designed and a collaborative work style.